Dopamine release in the dorsal striatum during cocaine-seeking behavior under the control of a drug-associated cue. - Ito, R; Dalley, J; Robbins, T; Everitt, B (2002)
Compulsive drug use is characterized by a pattern of drug seeking and consumption that becomes progressively habitual and less and less modifiable by external and internal factors. Although traditional views would posit that nigrostriatal dopamine (DA) neurons originating in the substantia nigra and innervating the dorsal striatum are primarily concerned with motor functions, recent studies have implicated the dorsal striatum in mediating stimulus-response (habit) learning. In this study, in vivo microdialysis in combination with a second-order schedule of cocaine reinforcement was used to investigate the role of the dorsal striatal dopamine innervation in well established drug-seeking behavior under the control of a drug-associated cue [light conditioned stimulus (CS+)]. Rats were initially trained to self-administer cocaine under a continuous reinforcement schedule where a response on one of two identical levers led to a 20 sec presentation of a light CS+ and an intravenous cocaine infusion (0.75 mg/kg). The response requirement for the CS+ and cocaine was then progressively increased until stable responding was established under a second-order schedule of reinforcement. During microdialysis, rats were presented with the cocaine-associated CS+ either noncontingently or contingent on responding during a session of cocaine-seeking behavior. The results showed a marked increase in DA release in the dorsal striatum during drug-seeking, when cocaine cues were presented contingently, but not when the same cue was presented noncontingently. These data indicate a possible involvement of the dopaminergic innervation of the dorsal striatum in well established, or habitual, cocaine-seeking behavior.